Factors Related to Completeness of Basic Immunization in Infants - Murani, Latifa (Jurnal Pinang Masak, 2024)
Immunization is an effective health maintenance effort to reduce the incidence of illness, disability and death. Completeness of basic immunization for babies can be influenced by various factors. Objective: This study aims to determine factors related to the completeness of basic immunization in infants. Method: This research is a quantitative descriptive correlation design research with a cross-sectional approach. The population in this study were mothers who had babies in the Rejosari Community Health Center Working Area. Sampling used Purposive Sampling technique with a total of 100 respondents. The analysis used is Spearman-rank analysis. Results: The research results showed that the characteristics of respondents aged 26-35 years were 63 respondents, the mother's highest educational level was secondary school (SMA) for 79 respondents and the mother did not work as many as 84 respondents, the distance to affordable health services was 72 respondents, received support from health workers there were 90 respondents and the completeness status of basic immunization for babies was complete for 87 respondents. Factors associated with completeness of maternal occupational immunization (p-value=0.018<0.05), distance to health services (p-value=0.026<0.05), and support from health workers (p-value=0.000<0 .05) Conclusion: There are three factors related to the completeness of basic immunization for babies, namely the mother's employment status, distance to health services and support from health workers. Suggestion: This research is expected to be a source of information and knowledge for the community, especially parents who have babies.